1996
DOI: 10.1021/om950727+
|View full text |Cite
|
Sign up to set email alerts
|

Facile Carbon−Carbon Bond Cleavage in an (η3-Cyclooctenyl)cobalt Complex Exhibiting Agostic C···H···Co Bonding

Abstract: The reaction of [(η5-C5Me5)Co(η4-1,5-cyclooctadiene)] with HBF4·Me2O affords, at room temperature, an agostic η3-cyclooctenyl complex which undergoes a facile ring opening to afford anti-[(η5-C5Me5)Co(η5-1-propylpentadienyl)]BF4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…Since C(2) and C(5) are not involved in the interaction with the agostic hydrogen, no additional splitting of a doublet resonance at δ 69.3 ppm is observed in the 13 C NMR spectrum of 5 . These observations are in accord with the idea that fluxional species 5 undergoes rapid metal-assisted 1,4-hydride shifts in solution . One may reasonably anticipate that an intramolecular fluxional process such as that observed for 5 in solution could likely proceed via an 18-electron diene-hydride intermediate, earlier depicted as B in Chart .…”
Section: Resultssupporting
confidence: 83%
“…Since C(2) and C(5) are not involved in the interaction with the agostic hydrogen, no additional splitting of a doublet resonance at δ 69.3 ppm is observed in the 13 C NMR spectrum of 5 . These observations are in accord with the idea that fluxional species 5 undergoes rapid metal-assisted 1,4-hydride shifts in solution . One may reasonably anticipate that an intramolecular fluxional process such as that observed for 5 in solution could likely proceed via an 18-electron diene-hydride intermediate, earlier depicted as B in Chart .…”
Section: Resultssupporting
confidence: 83%
“…Calculations on CoCp(η 3 -C 8 H 13 ), 2 , are consistent with the known crystal structure of 9 . There is no sign of an agostic interaction with a C−H bond adjacent to the Co-allyl unit (Figure ), even though the cationic Cp* analogue [CoCp*(η 3 -C 8 H 13 )] + (i.e., 8 + ) has been established to possess such an interaction . Addition of an electron to 17-electron 2 and optimization of the resulting 18-electron structure reveal that minor structural changes occur on reduction to [CoCp(η 3 -C 8 H 13 )] − ( 2 − ), the most significant of which is a small change in the position of the η 3 -cyclooctenyl ligand, which results in increased accessibility to a region of negative charge at the metal center (Figure ).…”
Section: Resultsmentioning
confidence: 79%
“…It is noteworthy that ESR spectra of 2 do not indicate any coupling to a H-atom that might indicate agostic interactions with C−H bonds adjacent to the allylic moiety to yield a 19-electron species. It has been demonstrated for the [CoCp*(η 3 -C 8 H 13 )] + cation (generated by protonation of 5 ) that an agostic interaction is present . In the [Rh(C 5 Ph 5 )(1,3-COD)], successive oxidations were stabilized by the formation of agostic interactions .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Two decades ago, Spencer et al, showed that upon protonation with HBF 4 Cp*Co­(η 4 -cyclopentadiene) and Cp*Co­(η 5 -cyclooctadiene) complexes undergo a suspiciously similar C–C bond cleavage reaction, yielding ring-opened cationic η 5 -pentadienyl complexes (eq ) . The possibility that such a bond activation could be embedded in the mechanism of the anomalous [3 + 2 + 2] cycloaddition reaction prompted us to investigate directly the reactivity of alkynes with acyclic pentadienyl complexes of cobalt.…”
Section: Introductionmentioning
confidence: 99%